Finite horizon analysis of autolanded aircraft in final approach under crosswind. (May 2022) - Biertümpfel, Felix; Pfifer, Harald
Abstract: The paper presents a worst-case touchdown performance analysis of auto-landed aircraft under complex wind disturbance. It takes advantage of the fact that the approaching aircraft effectively follows a predefined trajectory provided by the instrument landing system. Thus, the aircraft dynamics' linearization along the approach trajectory results in a finite horizon linear time-varying (LTV) representation. This naturally allows to include altitude triggered control law changes and changes in the flight dynamics, e.g., due to ground effect, in the analysis. To cover a broad range of environmental and aircraft parameter combinations in the worst-case analysis, a time-varying trajectory uncertainty description is introduced. The uncertainty's input/output behavior is covered by integral quadratic constraints. Thus, recent advances on the worst-case gain analysis of finite horizon LTV systems can be used. The corresponding analysis condition is based on a parameterized Riccati differential equation's solvability, which leads to a readily solvable nonlinear optimization problem. Applying the robust LTV framework, worst-cases for common touchdown criteria, such as vertical touchdown velocity, are calculated. These worst-cases cover the influence of complex wind fields and a large aircraft and environmental parameter set. The results are evaluated against corresponding Monte Carlo simulation on the original high fidelity, industry-sized nonlinear aircraft model. Highlights: Guaranteed worst-case analysis of touchdown constraints for autolanded aircraft. Application of the LTV IQC framework for complex autolanded aircraft benchmark model. Fast provision of upper bounds on Monte Carlo simulations.